Combination therapy is it in the future for successfully treating peripheral diabetic neuropathy? - Yorek, Mark (Frontiers in Endocrinology, 2024)
In 2022, the Center for Disease Control and Prevention reported that 11.3% of the United States population, 37.3 million people, had diabetes and 38% of the population had prediabetes. A large American study conducted in 2021 and supported by many other studies, concluded that about 47% of diabetes patients have peripheral neuropathy and that diabetic neuropathy was present in 7.5% of patients at the time of diabetes diagnosis. In subjects deemed to be prediabetes and impaired glucose tolerance there was a wide range of prevalence estimates (interquartile range (IQR): 6%-34%), but most studies (72%) reported a prevalence of peripheral neuropathy ≥10%. There is no recognized treatment for diabetic peripheral neuropathy (DPN) other than good blood glucose control. Good glycemic control slows progression of DPN in patients with type 1 diabetes but for patients with type 2 diabetes it is less effective. With obesity and type 2 diabetes at epidemic levels the need of a treatment for DPN could not be more important. In this article I will first present background information on the "primary" mechanisms shown from pre-clinical studies to contribute to DPN and then discuss mono-and combination therapies that have demonstrated efficacy in animal studies and may have success when translated to human subjects. I like to compare the challenge of finding an effective treatment for DPN to the ongoing work being done to treat hypertension. Combination therapy is the recognized approach used to normalize blood pressure often requiring two, three or more drugs in addition to lifestyle modification to achieve the desired outcome. Hypertension, like DPN, is a progressive disease caused by multiple mechanisms. Therefore, it seems likely as well as logical that combination therapy combined with lifestyle adjustments will be required to successfully treat DPN.